Marketing the arts : breaking boundaries - Kerrigan, Finola; Preece, Chloe (Abingdon, Oxon : Routledge, 2023)
"With contributions from international scholars of marketing and consumer studies, this renowned text engages directly with a range of contemporary themes, including: - The importance of arts consumption and its socio-political dimensions - The importance of the aesthetic experience itself, and how to research it - Arts policy development - The art versus commerce debate - The role of the arts marketer as market-maker - The artist as brand or entrepreneur This fully updated new edition covers digital trends in the arts and emerging technologies, including virtual reality, streaming services and branded entertainment. It also broadens the scope of investigation beyond the West looking to film in emerging markets such as India and China, music in Sub-Saharan Africa and indigenous art in Australia. Alongside in-depth theoretical analysis, this edition of Marketing the Arts has an enhanced focus on practical application, with updated case studies and tools throughout. Marketing the Arts: Breaking Boundaries, is core reading for advanced undergraduate and postgraduate students studying arts marketing and management. Online resources include chapter-by-chapter PowerPoint slides and a test bank"--
Arts Marketing, Social Justice Activism, and Government Messaging in the Age of Social Media / Francesca Sobande -- The Marketing of the Arts in the Age of Curatorial Production / Matthew Waters -- Virtual Reality, Film Marketing and Value / Stephanie Janes.
Keywords: Arts -- Marketing; BUSINESS & ECONOMICS / Marketing / General; ART / Business Aspects